Asuhan Keperawatan Pada An. D dengan Demam Thypoid di Ruang Anggrek 1 RSUD dr. Soeselo Kabupaten Tegal - Mega Ayu Nabila; Esti Nurjanah; Ahmad Zakiudin (Jurnal Ventilator, 2024)
Typhoid fever is an acute infection of the small intestine caused by Salmonella typhi, commonly occurring in developing countries with poor sanitation, including tropical regions such as Indonesia, where the climate supports the proliferation of this bacterium (Yustati & Dinata, 2023). The primary symptoms include high fever, nausea, abdominal pain, and gastrointestinal disturbances. This study employs a descriptive method with a case approach to identify and address nursing issues such as hyperthermia, knowledge deficit, and risk of nutritional deficit. The aim of this writing is to provide and describe comprehensive nursing care for typhoid fever patients at RSUD Dr. Soeselo, Tegal Regency, in accordance with established nursing standards, to ensure effective care and improved patient outcomes.